Desynchronization of Theta Oscillations in Prefrontal Cortex during Self-stimulation of the Medial Forebrain Bundles in Mice - Hwang, Eunjin; Lee, Heonsoo; Choi, Jee Hyun (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2018)
Stimulation of the medial forebrain bundle (MFB) can reinforce intracranial self-stimulation (ICSS) in rodents (i.e., reward-seeking behavior). The MFB stimulation produces a highly reliable behavioral output that enabled a clear distinction of the animal behavioral states between the non-ICSS and ICSS periods. However, the cortical states during these reward-seeking behaviors are not fully characterized in comparison to those during volitional behavior. This study was designed to characterize the cortical rhythms of and coherence between prefrontal cortex and hippocampus during the wheel-turning behavior reinforced by the ICSS in comparison to the wheel-turning without ICSS. We used a wheel for freely moving mice, which was programmed to deliver cathode currents through an electrode in the MFB at each one-quarter turn of the wheel to induce ICSS. The wheel-turning epochs were extracted from the pre-ICSS, ICSS and post-ICSS sessions and the prefrontal EEGs and the hippocampal LFPs in the epochs were analyzed with power and synchronization analyses. During the ICSS, the EEG power decreased at 6 similar to 10 Hz in the prefrontal cortex, while was not significantly altered in the hippocampus. Furthermore, we found that the phase synchrony between the prefrontal cortex and the hippocampus corresponding to information transmission between the two regions during reward-seeking motion decreased preceding MFB stimulation reinforced by ICSS. Our findings suggest that theta-activity can be reliably dissociated from active behavior if the animal is involved in self-stimulation.
Keywords: HIPPOCAMPAL EEG; BEHAVIOR; SYNCHRONY; MOVEMENT; SEEKING; MODEL; RATS